Study to Understand the Impact of Psychological Well-being on Young Managers - Duggal, Taranjeet; R ., Sujatha (International Journal of Psychosocial Rehabilitation, 2020)
Psychological well-being can be defined as levels of an individual’s positive functioning that include autonomy over their decisions, self-acceptance, personal or professional growth, positive relationships with others, and mastery over the environment. This concept is multidimensional and develops through a combination of identity, regulation of the emotions, characteristics of personality, and experiences of life. the Psychological wellbeing often increases with age, consciousness, extraversion and level of education. Stress can be defined as an emotional or physical response or reaction to any change that may be internal or external. It is an individual’s, brain and body’s reaction or response to an imagined or real threat, change or event. The event, threat or change are known as the stressors. Stressors could be external, such as any loss, unexpected change or tragedy, or internal, such as the beliefs, thoughts or attitudes. In this project, we studied about the relationship between psychological well-being and stress of young managers. The research was conducted by the help of responses collected by a questionnaire. The questionnaire was designed according to the variables and their subvariables with the help of "Carol Ryff Psychological Well Being " scale and statements covering variables other than those covered by the standardized questionnaire. The sample size for the research was100. A simple random sampling method was used in order to obtain the responses. The data was primarily collected from one location in the presence of the researcher. These responses were extracted to Microsoft Excel. For analysis of the data, descriptive statistics along with a higher statistical tool, SPSS, were used. Some findings from this study were that gender had slightly different results for psychological well-being and happiness. Some challenges faced by the researcher during the research were, like resistance from the potential respondents in filling out the questionnaire due to the length of the questionnaire. Since the standardized tool had reverse scoring, some responses were required to be reverse scored in order to obtain acceptable results from the responses, which is important for the analysis of data.